Sexual Behavior and Attitudes Toward Sex of Older Adults Living with HIV - Kriengkrai Srithanaviboonchai (2020)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. The number of older adults living with HIV (OALHIV) is increasing rapidly due to effective antiretroviral therapy. The current research describes sexual behavior, attitudes toward sex, and HIV transmission risk among OALHIV. Participants were HIV-infected persons aged 50 years and older enrolled from community hospitals in Chiang Mai Province, Northern Thailand. Of the 328 participants, 57.6% were women, and the average age was 58.8 years. The majority of participants (93.9%) had undetectable viral load. Most participants (77.1%) thought that it is ok/acceptable for PLHIV to have sex. About one-third of OALHIV participants were sexually active. Being male, younger, married, a previous smoker or a non-smoker, having a positive attitude toward sex, and not having a chronic health condition were independent predictors of having had sex in the last 12 months. Risk of HIV sexual transmission was likely low due to consistent condom use, undetectable viral load, and low instances of extramarital sex.